2010
DOI: 10.1161/circresaha.110.217117
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinase C Isoforms and Its Impact on Diabetic Complications

Abstract: Key Words: protein kinase C Ⅲ vascular cell biology Ⅲ diabetes Ⅲ cardiovascular diseases D iabetes currently affects nearly 170 million people worldwide and this number will double by 2030, affecting both developed and developing countries. 1 The major cause complications in diabetic patients is complications, which are the result of interactions among systemic metabolic abnormalities such as hyperglycemia, dyslipidemia, genetic and epigenetic modulators and local tissue responses to toxic metabolites. Complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
588
1
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 779 publications
(641 citation statements)
references
References 154 publications
(146 reference statements)
11
588
1
20
Order By: Relevance
“…6). It is well recognised that hyperglycaemia causes activation of PKCβ2 in the heart and subsequent activation of NADPH oxidase [29]. In the current study, PKCβ2 production and p22 phox expression were increased in diabetic Ntg hearts but not diabetic caPI3K hearts.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…6). It is well recognised that hyperglycaemia causes activation of PKCβ2 in the heart and subsequent activation of NADPH oxidase [29]. In the current study, PKCβ2 production and p22 phox expression were increased in diabetic Ntg hearts but not diabetic caPI3K hearts.…”
Section: Discussionsupporting
confidence: 45%
“…4a). A large body of evidence has demonstrated that hyperglycaemia leads to activation of PKCβ2 in the heart and subsequent activation of NADPH oxidase [29]. PKCβ2 protein production was increased in diabetic Ntg hearts compared with non-diabetic Ntg hearts (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Alternatively, redox imbalance can also lead to activation of PKC, which then would modulate expression of TGF-␤1. For instance, PKC activation is reversed by antioxidants and by administration of PKC inhibitors, and that reduces TGF-␤-mediated expression of ECM proteins and thereby ameliorates microvascular complications of diabetes (61,62). However, at this point, it is unknown whether the pathogenetic role of the G-X pathway in tubulo-interstitial fibrosis is mediated by the profibrogenic cytokine, TGF-␤1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and others reported previously that d-α-tocopherol prevents the activation of the DAG-PKC pathway in diabetic vascular tissues, including renal glomeruli through the enhancement of DGK (6,7,11), acting as a regulator of PKC activity (18). Thus, the activation of DGK may have therapeutic potential for preventing diabetic vascular complications.…”
Section: Discussionmentioning
confidence: 71%